PERSEPSI MAHASISWA AKUNTANSI TERHADAP PENERAPAN PAJAK KARBON DI INDONESIA - Kristian Mardaniasman Dakhi; Dudi Abdul Hadi (Jurnal Bisnis, Ekonomi, dan Sains, 2025)
This research aims to analyze accounting students' perceptions of the implementation of carbon tax in Indonesia based on gender and generation. The research was conducted descriptively. Samples were taken purposively from accounting students at Widyatama University, Bandung. Because the conditions of students at all universities are almost the same, namely that accounting students' perceptions of problems in the tax sector can indirectly influence students' desires to pursue a career in this field. The research results show that accounting students' perceptions of the implementation of carbon tax in Indonesia based on gender do not vary. Perceptions of accounting students based on class also do not vary. However, accounting students' perceptions of the implementation of carbon tax in Indonesia are determined by gender and class factors.